PROFESSIONAL TOLERANCE AS A COMPONENT OF FOREIGN LANGUAGE LECTURERS’ READINESS TO CREATIVE PROFESSIONAL WORK AT UNIVERSITIES - Balakhtar, Kateryna (PSYCHOLOGICAL JOURNAL, 2019)
In today’s conditions, special attention is required to the professional tolerance of foreign language lecturers, which is a component of their readiness to creative professional work at university and requires proper training, inclusion into various spheres of public relations and professional work. Professional tolerance is a personal quality; it involves an active attitude towards others, based on the recognition of universal human rights and fundamental freedoms, respect, acceptance and correct understanding of the rich diversity of cultures of our world; it also mean self-expression and manifestation of human personality, readiness and ability to have an equal dialogue at university with synergetic interactions, developed tolerance to participants of the educational process, formed critical thinking, when each person is valued, but, at the same time, own ideological positions and value orientation are created. The applied main principles of tolerance (trust cooperation, ecology of relations, self-esteem, self-respect, respect for others, society, synergism, creativity) ensure different used approaches to establishing of tolerant relationships and help to analyze interactions at university and to form some qualities (characteristics or properties) that foreign language lecturers must acquire. The structure of the foreign language lecturers’ readiness for professional work (motivational, value, cognitive, affective, activity, reflexive components) is revealed. The conditions supporting development and formation of foreign language lecturers' professional creativity are highlighted. Creativity at educational process, professional competence, tolerance, work capability, qualification, the value-motivational, cognitive, affective, activity-reflective spheres, etc., depend directly on a foreign language lecturer, who should be a creative, tolerant person, possess the necessary “arsenal” of methods, technologies and be prepared to effective professional work at university.